Implementation of a salt substitute intervention using social marketing in resourced-limited communities in Peru: a process evaluation study - María Lazo-Porras; María Lazo-Porras; Adela Del Valle; David Beran; Maria Amalia Pesantes; Maria Amalia Pesantes; Silvana Perez-Leon; Vilarmina Ponce-Lucero; Antonio Bernabe-Ortiz; María Kathia Cárdenas; François Chappuis; Pablo Perel; et al. (Frontiers Media S.A., 2023)
ObjectiveThis study aimed to conduct a process evaluation of a salt substitute trial conducted in Peru.MethodsThrough semi-structured interviews of intervention participants, we documented and analyzed process evaluation variables as defined by the Medical Research Council Framework. This study was a stepped wedge trial conducted in Tumbes, Peru in 2014. The intervention was a community-wide replacement of regular salt (100% sodium) with "Salt Liz" (75% sodium and 25% potassium) using social marketing strategies to promote the adoption and continued use of the salt substitute in daily life. The components of the social marketing campaign included entertainment educational activities and local product promoters ("Amigas de Liz"). Another component of the intervention was the Salt Liz spoon to help guide the amount of salt that families should consume. The process evaluation variables measured were the context, mechanism of action, and implementation outcomes (acceptability, fidelity and adoption, perceptions, and feedback).ResultsIn total, 60 women were interviewed, 20 with hypertension and 40 without hypertension. Regarding context, common characteristics across the four villages included residents who primarily ate their meals at home and women who were responsible for household food preparation. As the mechanism of action, most participants did not notice a difference in the flavor between regular salt and Salt Liz; those that did notice a difference took around 2 weeks to become accustomed to the taste of the salt substitute. In terms of implementation outcomes, the Salt Liz was accepted by villagers and factors explaining this acceptability included that it was perceived as a "high quality" salt and as having a positive effect on one's health. Participants recognized that the Salt Liz is healthier than regular salt and that it can help prevent or control hypertension. However, most participants could not accurately recall how the compositions of the Salt Liz and regular salt differed and the role they play in hypertension. Although the use of the Salt Liz was far-reaching at the community level, the use of the Salt Liz spoon was poor. Educational entertainment activities were well-received, and most participants enjoyed them despite not always being active participants but rather sideline observers.ConclusionThis process evaluation identifies key intervention components that enabled a successful trial. Seeking and incorporating feedback from the target population helps deepen the understanding of contextual factors that influence an intervention's success. Furthermore, feedback received can aid the development of the intervention product. Some factors that can be improved for future interventions are acknowledged.Clinical trial registrationNCT01960972.